Interaction of polymorphonuclear leukocytes and viruses in humans: adherence of polymorphonuclear leukocytes to respiratory syncytial virus-infected cells. - Faden, H (1984)
The nature of neutrophil-respiratory syncytial virus (RSV) interaction was investigated by assessing factors that influence neutrophil adherence to RSV-infected tissue culture monolayers. The adherence of neutrophils to infected cells was directly proportional to the degree of RSV replication as evidenced by infectious virus production, cytopathological changes, or viral antigen appearance. Sixty-one percent of the neutrophils adhered to the RSV-infected cells as compared with 52.7% on noninfected monolayers (P less than 0.05). The addition of RSV-specific antibody markedly increased polymorphonuclear leukocyte adherence to 88.5% (P less than 0.001). Complement in the absence of antibody augmented polymorphonuclear leukocyte adherence, but to a lesser degree, 69.0% (P less than 0.025). Arachidonic acid metabolism appeared to play a critical role in the adherence process; thromboxane was the single most important arachidonic acid metabolite. Inhibition of thromboxane synthesis reduced antibody-dependent polymorphonuclear leukocyte adherence on RSV-infected cells to 52.3% (P less than 0.025). These observations suggest a role for neutrophils in RSV infection. It is proposed that neutrophils may participate in RSV infection at the site of viral replication through the attachment to infected cells and the subsequent release of mediators of inflammation.